Visual and Acoustical Social Displays by the Grasshopper Arphia Conspersa (Orthoptera: Acrididae) - Robert B. Willey; Ruth L. Willey (Psyche: A Journal of Entomology)
Many species of the Oedipodinae (band-wing grasshoppers) exhibit strikingly diverse social interactions invoking visual and acoustical communication between the sexes and between individuals of the same sex (Otte, 1968, 1969).